CYCLIC BEHAVIOR AND CRITICAL PART OF ECCENTRIC BRACED FRAMES WITH VERTICAL LINKS - Susanti, Lilya; Wijaya, Ming Narto; Wiranatha, I Gde Eka; Jallow, Abdourahim (Journal of Applied Engineering Science, 2024)
A vertical shear link-equipped reinforced concrete eccentric braced frame (RC-EBF) exhibits a unique behavior that has yet to receive much research. The vertical shear link is located separately from the main beam, so it does not interfere with its performance. Moreover, it gives structural retrofitting flexibility. To comprehend the structural strength of EBF compared to Concentric Braced Frames (CBF), the current work explored the cyclic deformation history of RC-EBF type Y (vertical shear links). It also sought to identify the critical frame components contributing to structural failure. The investigation involves nine specimens comprising CBF and EBF with 15 cm and 25 cm vertical linkages.  Cyclic load-displacement histories revealed that the CBF configuration is the stiffest and most reliable one. The CBF structure exhibits equal deformation at higher cyclic loads than the EBF. Shear stress is the critical factor contributing to the structure's collapse, as demonstrated by the diagonal main crack in the current EBF samples.
Keywords: cyclic load, deformation, eccentrically braced frames, reinforced concrete, vertical shear link